Pengaruh Stabilitas Penjualan dan Struktur Aktiva Terhadap Struktur Modal: Studi Empiris pada Perusahaan Sub Sektor Perdagangan Besar (Barang Produksi dan Barang Konsumsi) yang terdaftar di Bursa Efek Indonesia Periode Tahun 2013-2017 - Jaenal Abidin; Ilham Hidayat (Politeknik Ganesha Medan, 2019)
The purpose of this study was to determine the effect of sales stability on the capital structure and to determine the effect of asset structure on capital structure and to determine the effect of sales stability and asset structure together on capital structure in large trading sub-sector companies (production goods and consumer goods ) period 2013-2017.The type of research used is quantitative associative, with the method of collecting data using secondary data obtained from the Indonesia Stock Exchange. The population in this study are large-scale trade sub-sector companies (production goods and consumer goods) listed on the Indonesia Stock Exchange. Sampling using the purposive sampling method, there are 45 samples. The method of analysis uses multiple linear regression. The results of the study can be concluded that sales stability has a significant effect on capital structure, asset structure has a significant influence on capital structure, and sales stability and asset structure together (simultaneously) affect the capital structure